The suppressive efficacy of THZ1 depends on KRAS mutation subtype and is associated with super‐enhancer activity and the PI3K/AKT/mTOR signalling in pancreatic ductal adenocarcinoma: A hypothesis‐generating study - Lei Huang; Hui Yang; Kaidi Chen; Jing Yuan; Jie Li; Guanghai Dai; Mancang Gu; Yan Shi (Clinical and Translational Medicine, 2023)
Abstract Background Inhibition of CDK7, a potent transcription regulator, may bring new hope for treating pancreatic ductal adenocarcinoma (PDAC), which is featured by large genetic heterogeneity and abundant KRAS mutations. This investigation aimed at exploring the discrepant efficacies of THZ1, a small‐molecule covalent CDK7 inhibitor, on PDACs with different KRAS mutations and the underlying mechanisms. Methods Associations of CDK7 expression with survival by KRAS mutations were first assessed. Effects of THZ1 on PDAC by different KRAS mutations were then investigated in vitro and in vivo. Moreover, the effects of THZ1 on gene transcription and phosphorylation of RNA polymerase II (RNAPOLII) in different KRAS mutant PDACs were assessed, and the effect of THZ1 on super‐enhancer activity was evaluated using chromatin immunoprecipitation sequencing. Lastly, the effects of THZ1 on the binding of H3K27ac to PIK3CA and on the PI3K/AKT/mTOR signalling were analysed. Results High CDK7 expression was significantly linked to worse survival within PDAC patients carrying KRAS‐G12V mutation but not in those with KRAS‐G12D mutation. The apoptosis‐inducing effect of THZ1 was markedly stronger in KRAS‐G12V PDAC than KRAS‐G12D cancer. THZ1 significantly inhibited the growth of xenograft tumour with KRAS‐G12V mutation, and the inhibition was markedly stronger than for KRAS‐G12D tumour. In mini‐cell‐derived xenograft (CDX) models, THZ1 significantly suppressed KRAS‐G12V PDAC but not KRAS‐G12D cancer. THZ1 significantly suppressed the phosphorylation of RNAPOLII, and this effect was stronger in KRAS‐G12V PDAC (especially at ser5). KRAS‐G12V PDAC had more H3K27ac‐binding super‐enhancers, and the inhibition of THZ1 on super‐enhancer activity was also stronger in KRAS‐G12V PDAC. Furthermore, THZ1 significantly weakened the binding of H3K27ac to PIK3CA in KRAS‐G12V PDAC. THZ1 significantly suppressed the PI3K/AKT/mTOR pathway and its downstream markers, and this effect was stronger in KRAS‐G12V cells. Conclusions In this hypothesis‐generating study, THZ1 might selectively inhibit certain PDACs with KRAS‐G12V mutation more potently compared with some other PDACs with KRAS‐G12D mutation, which might be associated with its effect on super‐enhancer activity and the PI3K/AKT/mTOR signalling. Our findings might offer novel key clues for the precise management of PDAC and important evidence for future targeted trial design. Highlights THZ1 had a stronger effect on PDAC‐bearing KRAS‐G12V mutation than G12D mutation. Suppressive effect of THZ1 on phosphorylation of RNAPOLII was stronger in KRAS‐G12V than KRAS‐G12D PDAC. Inhibition of THZ1 on super‐enhancer activity and H3K27ac binding to PIK3CA was stronger in KRAS‐G12V PDAC. Suppressive effect of THZ1 on PI3K/AKT/mTOR pathway was stronger in KRAS‐G12V PDAC.